Information technology. Digital compression and coding of continuous-tone still images. Registration of JPEG profiles, SPIFF profiles, SPIFF tags, SPIFF colour spaces, APPn markers, SPIFF compression types, and Registration Authorities (REGAUT) Part 4, (15th October 1999) - British Standards Institution,
No abstract available